2022
DOI: 10.1111/head.14360
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the structure and function of the brain in adolescents with new daily persistent headache: A pilot MRI study

Abstract: Objective The purpose of this study was to explore brain morphological and functional connectivity alterations in adolescents with new daily persistent headache (NDPH) compared to pain‐free, healthy controls. Background NDPH is one of the most disabling and least understood primary headache conditions. To date, no studies have considered the role of brain function and structure in pediatric patients with NDPH. Methods In this cross‐sectional study, resting‐state functional and structural images were acquired f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…Given an anticipated dropout rate of 20%, the total sample size required is 36 cases (18 HC group and 18 CM group). Fifteen NDPH cases were included in this study according to the previous similar studies [10, 21,22,33,34]. To match the age and sex of patients with NDPH, 15 HC and 18 patients with CM were included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given an anticipated dropout rate of 20%, the total sample size required is 36 cases (18 HC group and 18 CM group). Fifteen NDPH cases were included in this study according to the previous similar studies [10, 21,22,33,34]. To match the age and sex of patients with NDPH, 15 HC and 18 patients with CM were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patients with NDPH had no structural brain changes [36]. Another study of adolescent found that patients with NDPH reduced cortical thickness in the bilateral superior temporal gyrus, left superior, and middle frontal gyrus areas compared with controls [34]. There is still some controversy regarding the alteration of NDPH structure.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional voxel-based morphometry (VBM) and surface-based morphometry (SBM) study investigated 23 patients with NDPH and 23 age- and gender-matched healthy controls (HCs) and found no grey matter changes in patients with NDPH [ 32 ]. Another cross-sectional study in 13 adolescents with NDPH found reduced cortical thickness in the bilateral superior temporal gyrus, left superior, and middle frontal gyrus areas and altered functional connectivity in the amygdala, insula, frontal regions, and cerebellar subregions compared to 13 HCs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a substantial leap forward in studying this condition. So far in adults, no structural imaging changes have been noted; however, in a pediatric population with NDPH, there were unique alterations compared to age-matched controls, including a reduction in thickness in the left superior frontal gyrus, cortical thinning in the temporal and middle frontal gyrus, and altered functional connectivity between certain brain regions (51,52). The issue with these studies, however, is that they regard NDPH as a single homogenous entity which it is not; so, the study results have to be interpreted with some caution.…”
Section: Pathogenesismentioning
confidence: 99%